Peningkatan literasi dampak dan pencegahan stunting masyarakat lahan gambut Desa Banglas Barat, Kepulauan Meranti - Yelly Zamaya; Arifudin Arifudin; Agil Syafni Prakoso (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Stunting is currently a major concern for both central and regional governments, as the health of children is the primary indicator used to make decisions about the quality of public health. One of the factors that continues to contribute to stunting is a lack of parental literacy in early prevention, which has a significant impact on parenting and child development monitoring. Stunting is caused primarily by a lack of optimal nutritional intake during pregnancy and after birth, as well as a lack of access to medical services and clean water and sanitation facilities. This activity took place in Banglas Barat Village, Kepulauan Meranti Regency, because the village was designated as one of the stunting loci in 2022. This village has peatland and an island area, so it has different land contours and food sources than other lands that do not have peat. As a result, special attention is required to prevent stunting. The goal of service activities is to raise public awareness about stunting. This activity included the distribution of brochures on the effects and prevention of stunting, as well as the creation of banners in the center of Banglas Barat Village.